Targeting Inflammation Across the Myocardial Infarction Continuum: Biomarkers, Imaging, and Emerging Therapies - Kristi Hoxha; Isabella Maccaferri; Francesco Paparazzo; Alberto Sarti; Giorgio Sciaramenti; Giovanni Camaiti; Pierpaolo Cioci; Cristina Rizza; Renè Tezze; Ludovica Rita Vocale; Elisabetta Tonet; Federico Marchini; et al. (Journal of Clinical Medicine, 2026)
Background: Myocardial infarction (MI) remains a leading cause of morbidity and mortality despite major advances in reperfusion and secondary prevention. Inflammation contributes throughout the MI continuum, from atherosclerotic plaque development and destabilization to myocardial injury, adverse ventricular remodeling, and recurrent cardiovascular events. Objective: This narrative review summarizes current evidence on inflammation across the MI continuum, focusing on inflammatory biomarkers, cardiovascular imaging, residual inflammatory risk, and emerging anti-inflammatory therapies. Methods: We reviewed current evidence on the pathophysiological and clinical relevance of inflammation in MI, with particular emphasis on circulating biomarkers, multimodality imaging, and inflammation-targeted therapeutic strategies. Results: High-sensitivity C-reactive protein remains the best-established biomarker of residual inflammatory risk, while interleukin-6, myeloperoxidase, suPAR, and GlycA provide complementary information. Advanced imaging, including coronary computed tomography-derived perivascular fat attenuation index, cardiac magnetic resonance, and positron emission tomography, may further characterize vascular and myocardial inflammation. Clinical trials support inflammation as a potentially modifiable component of cardiovascular risk; however, therapeutic benefit has been inconsistent across inflammatory targets, agents, and clinical settings. Canakinumab and low-dose colchicine have demonstrated cardiovascular benefit in selected secondary-prevention populations, although recent neutral trials highlight heterogeneity across clinical settings. Similarly, IL-6-targeted strategies have yielded mixed results, with the neutral ZEUS trial underscoring that biomarker reduction does not necessarily translate into cardiovascular benefit, while NLRP3-targeted approaches remain investigational. Conclusions: Integrating inflammatory biomarkers, multimodality imaging, and targeted therapies may improve risk stratification and support personalized secondary prevention. Further evidence is needed to define optimal patient selection and determine whether biomarker- or imaging-guided anti-inflammatory strategies improve clinical outcomes.